Stable algorithm for event detection in event-driven particle dynamics: logical states - Strobl, Severin; Bannerman, Marcus; Pöschel, Thorsten (Computational Particle Mechanics, 2016)
Following the recent development of a stable event-detection algorithm for hard-sphere systems, the implications of more complex interaction models are examined. The relative location of particles leads to ambiguity when it is used to determine the interaction state of a particle in stepped potentials, such as the square-well model. To correctly predict the next event in these systems, the concept of an additional state that is tracked separately from the particle position is introduced and integrated into the stable algorithm for event detection.
Keywords: DEM; Event-driven; Molecular dynamics; Square well; Stepped potential; Collision detection